To compare and evaluate the anti-inflammatory efficacy of terminalia arjuna (aqueous extract of bark) with diclofenac sodium on rats - Rana, Maninder Singh; Walia, Rani; Dixit, Alok; Raina, Kaustubh (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Terminalia arjuna is a well-known Indian medicinal plant whose bark is extensively used in ayurvedic medicine. It is one of the most versatile medicinal plants having a wide spectrum of biological activity. The objective of this study was to study and evaluate the anti-inflammatory activity of Terminalia arjuna on carragennan induced paw edema in sprague dwaley rats. Methods: Terminalia arjuna aqueous extract of bark in 200, 400 and 800mg/kg doses were administered to sprague dawely rats prior to induction of carrageenan induced paw edema. Statistical analysis: was done by using student t test. P < 0.05 was considered statistically significant. Results: Only 400mg/kg dose of Terminalia arjuna aqueous extract of bark was able to decreases the size of paw edema at significant levels in carrageenan induced paw edema in rats. Conclusions: The aqueous extract of bark of Terminalia arjuna possesses anti-inflammatory activity on carrageenan induced paw edema in rat model.